Psychological Burden and Diabetes Self-Management Behaviour Among Northern Saudi Adults with Type 2 Diabetes: A Cross-Sectional Study - Aseel Awad Alsaidan (Healthcare, 2026)
Background and objectives: Type 2 diabetes mellitus (T2DM) care depends on sustained self-management behaviour and psychological wellbeing. This study examined diabetes self-management behaviour, depressive symptom burden, and associated demographic factors among adults with T2DM. Methods: The present cross-sectional study was conducted among T2DM patients attending 10 primary healthcare centres in the Al-Jouf region, northern Saudi Arabia. Diabetes self-management behaviour was assessed using the Summary of Diabetes Self-Care Activities, and depressive symptoms were assessed using Patient Health Questionnaire-9. Binomial logistic regression identified factors associated with low self-management behaviour and no-to-mild depressive symptom status. Results: Of the 350 T2DM patients studied, the mean self-care activity score was 28.38 ± 12.10, and the mean PHQ-9 score was 6.39 ± 3.91. Moderate-to-severe depressive symptoms were present in 87 participants (24.9%). Low self-management behaviour was significantly associated with obesity (Ref: normal body mass index; AOR: 1.47, 95% CI: 1.10–2.06, p = 0.041), T2DM duration of 6–10 years (Ref: 0–5 years; AOR: 2.12, 95% CI: 1.18–3.83, p = 0.013), other chronic illnesses (Ref: no; AOR: 1.93, 95% CI: 1.18–3.16, p = 0.004), and moderate-to-severe depressive symptoms (Ref: none-to-mild; AOR: 1.76, 95% CI: 1.21–3.06, p = 0.034). Conclusions: Suboptimal diabetes self-management behaviour and depressive symptom burden were observed. Integrating structured self-management education, repeated behavioural counselling, and depressive symptom screening may improve patient-centred diabetes care.